2023
DOI: 10.26508/lsa.202201802
|View full text |Cite
|
Sign up to set email alerts
|

HR repair pathway plays a crucial role in maintaining neural stem cell fate under irradiation stress

Abstract: Environmental stress can cause mutation or genomic instability in stem cells which, in some cases, leads to tumorigenesis. Mechanisms to monitor and eliminate these mutant stem cells remain elusive. Here, using theDrosophilalarval brain as a model, we show that X-ray irradiation (IR) at the early larval stage leads to accumulation of nuclear Prospero (Pros), resulting in premature differentiation of neural stem cells (neuroblasts, NBs). Through NB-specific RNAi screenings, we determined that it is the Mre11–Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…Interestingly, earlier work has shown that deletion of Atr in adult mice leads to depletion of stem and progenitor cells ( 63 ), that has been suggested to arise due to aberrant, ectopic differentiation. This hypothesis is supported by a recent report in the fruitfly, which identified a critical role for Drosophila ATR ( mei-41 ) in preventing neuroblast differentiation in response to irradiation stress ( 64 ). Interestingly, inhibition of the ATR and ATM DDR kinases has been linked with differentiation in acute myeloid leukemia cells carrying MLL fusion proteins, where treatment with ATR inhibitors led to terminal differentiation and loss of leukemic blasts ( 65 , 66 ).…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, earlier work has shown that deletion of Atr in adult mice leads to depletion of stem and progenitor cells ( 63 ), that has been suggested to arise due to aberrant, ectopic differentiation. This hypothesis is supported by a recent report in the fruitfly, which identified a critical role for Drosophila ATR ( mei-41 ) in preventing neuroblast differentiation in response to irradiation stress ( 64 ). Interestingly, inhibition of the ATR and ATM DDR kinases has been linked with differentiation in acute myeloid leukemia cells carrying MLL fusion proteins, where treatment with ATR inhibitors led to terminal differentiation and loss of leukemic blasts ( 65 , 66 ).…”
Section: Discussionsupporting
confidence: 61%
“…This loss of stem and progenitor cells has been suggested to arise due to elevated apoptosis or senescence, however, no differences could be observed between Atr -deficient and control tissues, raising the possibility that deletion of Atr triggered aberrant, ectopic differentiation, leading to the loss of proliferating stem and progenitor cells. This hypothesis is supported by a recent report in the fruit fly, Drosophila melanogaster , that identified a critical role for Drosophila ATR ( mei-41 ) in preventing neuroblast differentiation in response to irradiation stress 64 .…”
Section: Discussionsupporting
confidence: 53%
“…Conversely, knocking down all HR repair pathway genes (such as RAD50, Nbs) leads to significantly enhanced premature differentiation of NSCs, which is indicative of premature ageing. These findings suggest that HR plays an important role in NSCs DDR when NHEJ is nonfunctional (Xu et al, 2023). It is also demonstrated that NSCs, when subjected to destruction of Rad54 (homologous recombination factor), led to a stagnant phase in the G2/S and extended S phase.…”
Section: Dna Damage Causes Inflammation and Ageing Of Nscsmentioning
confidence: 80%
“…When exposed to low levels of radiation, NSCs tend to differentiate prematurely rather than undergo apoptosis like most differentiated cells, indicating their tolerance to DNA damage. NSCs exhibit higher DNA damage tolerance compared to differentiated cells (Xu et al, 2023). Liu Z et al found that Dgcr8 −/− NSCs did not show increased apoptosis, but they did after differentiation into neurons or oligodendrocytes.…”
Section: Dna Damage Tolerance Of Nscsmentioning
confidence: 99%